(untitled) (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Putra IPYA, Utami KS, Hardini J, Wirasuta IMAG, Ujam NT, Ariantari NP. 2023. Fermentation, bioactivity and molecular identification of endophytic fungi isolated from mangrove Ceriops tagal. Biodiversitas 24: 3091-3098. Mangrove-associated-endophytic fungi are recognized as a considerable source of bioactive compounds in drug discovery. This study evaluated the antimicrobial activity and toxicity of endophytic fungi isolated from Ceriops tagal. Four endophytic fungal isolates, documented as SU-1-4, were obtained. In addition, isolate SU-3 was further identified as Hypoxylon mangrovei according to the comparison of the internal transcribed spacer region. Each fungal isolate was fermented on a solid rice medium, then extracted with ethyl acetate at the end of fermentation. After that, the crude ethyl acetate extracts were partitioned between aqueous methanol and n-hexane, and the methanolic phases were subjected to phytochemical screening and antimicrobial and toxicity assays. Preliminary phytochemical identification suggested the presence of alkaloids, triterpenoids, and steroids in all fungal methanolic extracts. Among them, H. mangrovei SU-3 extract showed the most pronounced antimicrobial effects with minimum inhibitory concentration (MIC) values of 125 and 250 µg.mL-1 towards Staphylococcus aureus ATCC 6538 and Staphylococcus epidermidis ATCC 12228. Meanwhile, the toxicity assay employing the brine shrimp lethality test revealed that all fungal methanolic extracts were toxic, with LC50 values ranging from 173.09 to 227.76 µg.mL-1. Isolation of antibacterial compounds and evaluation of their cytotoxicity on human cancer cells will be promising for further studies.